INTELLECTUAL CAPITAL OF INDONESIAN STATE-OWNED ENTERPRISES AND PROFITABILITY AND COMPANY AGE AS MODERATING VARIABLES - Rachmawati, Rima; Fadhilah, Nona Ratu Soraya Syahsyarifah; Rusmiyatie, Mia; Nugrahani, Shinta Lidia; Ariesti, Annisya Herbi; Herman, Alwan Dzaki Fadhillah (CENTRAL ASIA AND THE CAUCASUS, 2022)
This purpose of this study is to answer phenomenon declining financial performance in State-Owned Enterprises (SOEs) due to low awareness of managing intellectual capital, as well as the age of the company as a moderating variable that can strengthen the correlation between the two. Intellectual capital is measured using Pulic's concept with the term Value Added Intellectual Capital (VAIC). Meanwhile, financial performance measured based on the return on assets. Research design: quantitative research method was employed to answer the hypothesis by using an explanatory method approach, on 51 SOEs. Findings: The results of the study found no evidence its intellectual capital might affect the financial performance of SOEs in 2019. Even when the age of the company acted as a moderating variable, there was still no evidence. Originality. This study has a novelty value in terms of including the moderator variable, namely the age of the company, which has never been studied before.